الابعاد التداولية للاستعارة في قصائد محمود درويش - كناب, زهيرة (كلية الأدب العربي والفنون, 2024)
تحاول هذه الدراسة الموسومة بالأبعاد التداولية للاستعارة في قصائد محمود درويش: الإحاطة بإجراءات الفكر التداولي واستكشاف الطريقة التي يستخدم بها محمود درويش الاستعارة كأداة شعرية. لا لنقل المعاني بصورتها المباشرة فحسب بل لبناء تفاعلات مركبة وحوارين الشاعر وقارئه، ولا يستعان بالاستعارات فقط لتجميل النص، ولكن كطريقة لتقديم أفكار معقدة وتجارب حياتية من خلال إيحاءات ودلالات غير مباشرة تستلزم من المتلقي التفاعل مع النص وتفسيره ضمن سياقه الثقافي والسياسي This study, entitled The Pragmatic Dimensions of Metaphor in Mahmoud Darwish’s Poems, attempts to understand the procedures of pragmatic thought and explore the way in which Mahmoud Darwish uses metaphor as a poetic tool. Not only to convey meanings directly, but to build complex interactions and dialogue between the poet and his reader. Metaphors are not used only to beautify the text, but as a way to present complex ideas and life experiences through indirect suggestions and connotations that require the recipient to interact with the text and interpret it within its cultural and political context.
Keywords: - الأبعاد التداولية - الاستعارة - السياق - المتلقي - إجراءات الفكر التداولي; - Pragmatic dimensions - metaphor - context - recipient - procedures of pragmatic thought.